The Effects Of Oral Communicative Activity And Foreign Language Anxiety On Willingness To Communicate In English In Malaysian Based Libyan Schools - Alkilani, Rema Ali Masaud (2023)
The present study investigates the effects of oral communicative activity, foreign language anxiety and enjoyment on willingness to communicate in English among 68 Grade Nine students in Malaysian-based Libyan schools. The study seeks to determine the correlations between these variables and compare the differences in speaking performance before and after implementing the oral communicative activity